2011
DOI: 10.1177/070674371105600205
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Conditions and Behavioural Problems in Adolescents with Intellectual Disabilities: Correlates with Autism

Abstract: Objective: To determine whether psychiatric and behavioural disorders occur more frequently in adolescents with autism and intellectual disabilities, compared with those without autism. Method:A population-based case-control study was undertaken and 36 adolescents with autism were pairwise matched for age and IQ to 36 adolescents without autism. Caregivers were interviewed with structured psychiatric interview and questionnaire measures of psychiatric and behavioural problems. Results:Compulsive behaviours and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Studies have shown that the prevalence rates of behavioural and emotional problems in children with ASD are much higher than those in the general populations (Ghaziuddin et al., 1992; Horner et al., 2002; Ooi et al., 2011). Some of these problems are possibly due to the manifestations of their anxiety, fears, phobias and/or stereotyped behaviours (Bradley et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prevalence rates of behavioural and emotional problems in children with ASD are much higher than those in the general populations (Ghaziuddin et al., 1992; Horner et al., 2002; Ooi et al., 2011). Some of these problems are possibly due to the manifestations of their anxiety, fears, phobias and/or stereotyped behaviours (Bradley et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 30-64% of children and adolescents with ID develop comorbid mental health disorders, a rate of 2.8-4.5 times that of their peers in the general population, including higher rates of depression, anxiety and psychosis. 7-11 Persons with ID have been reported to experience more abuse, neglect, social disadvantage, challenging family circumstances, stigma, peer neglect and peer exclusion than persons without such disabilities. 12-14 The “dual diagnosis 15 ”of mental illness and ID is often missed by clinicians due to a general under-identification of emotional and mental health problems in persons with ID 16,17 Given the common occurrence of this diagnostic overshadowing along with the cognitive, physical and psychiatric vulnerabilities outlined above, persons with ID are likely to be at increased risk for undetected suicidal thoughts and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a body of literature indicates that intelligence is related to ASD symptom severity (e.g. Bradley et al, 2011; Eagle et al, 2010; Stevens et al, 2000; Witwer and Lecavalier, 2008). All in all, the relationship between IQ and anxiety in ASD has not been settled definitively.…”
Section: Introductionmentioning
confidence: 99%